THE ROLE OF RELATIONSHIP LEARNING AND MARKETING STRATEGY AS MEDIATORS OF SERVICE INNOVATION ON THE IMPACT OF SALES PERFORMANCE OF CAR DEALERS IN THE SURAKARTA CITY - Yoga Tegar Firmansyah; Aflit Nuryulia Praswati (SEAN Institute, 2023)
As we know today, competition in the industrial world is becoming increasingly fierce, especially in the automotive industry. Therefore, the company's management strives to always provide the best service by creating new products that meet the needs and desires of its customers. Companies that can innovate their services, have a good relationship with consumers, and do an excellent marketing job can undoubtedly improve the performance of their product sales. This service innovation is needed by companies in the automotive industry, especially car dealers, to carry out the process of developing their service innovation to increase sales value. Therefore, the research study aims to examine the influence of service innovation on sales performance in automotive firms, especially car dealers. However, few empirical studies have examined the outcomes of firms' involvement in service innovation. There needs to be more convincing arguments for firms to innovate their services to improve sales performance by incorporating the role of relationship learning and marketing strategy. To fill the gap in previous research, the current work can explore the mechanisms between service innovation and sales performance. A survey was conducted using non-probability and purposive sampling techniques, with the criteria being car owners and salespeople in Surakarta. With a total final sample of 100 completed surveys and hypothesis testing using Partial Least Square-Structural Equation Modelling (PLS-SEM). The results show that the service innovation variable can influence sales performance. The increase in sales value is also influenced by mediator variables, namely relationship learning and marketing strategy. Against the background of Service-Dominant Logic (SDL), findings contribute to the literature on service innovation for automobile distribution companies, which shows that increasing service innovation requires a complete understanding of the following factors.